Analysis of playing style across different developmental stages in football. (2nd November 2021) - Dayus, Jacob; Callaway, Andrew; Ellis, Shelley; Butterworth, Andrew
ABSTRACT: Notational analysis research to date has often overlooked Youth football, predominantly examining First teams in elite competitions. As a result, the current study aims to compare performance between U16s, U18s and First teams. 3311 final third entries were analysed over the course of 45 matches, equally distributed across three age-groups, during the 2018–2019 season. The sample consisted of 10 U16 teams, 16 U18 teams and 16 First teams. The study found that there were significant differences in playing styles across the age groups. As experience increases, there is a tendency of more wing than central attacks, more forward-diagonal movements, more crosses, but fewer shooting opportunities due to developments in defence abilities. The differences in the patterns of play across the age groups, suggests that younger players are more independently focused when attempting to breakdown their opposition's defence, with older teams using space more effectively and more team focused.